A passion for performance : Sarah Siddons and her portraitists / edited by Robyn Asleson. - Asleson, Robyn (J. Paul Getty Trust, 2001)
This work explores the life and career of Sarah Siddons, the famed English actress who revolutionized 18th-century English theatre. The book includes 55 portraits of Siddons by artists such as Thomas Gainsborough and George Romney.